Starch biopolymer films containing chitosan nanoparticles: a review - Othman, Siti Hajar; Shapi'i, Ruzanna Ahmad; Ronzi, Nur Diana Arisya; Abd Rashid, Norhashima (Elsevier, 2024)
Starch biopolymer films incorporated with chitosan nanoparticles (CNP) or starch/CNP films are promising alternatives to non-degradable food packaging materials. The films can be utilized for active food packaging applications because CNP exhibits antimicrobial and antioxidant properties, which can improve food shelf-life. Nonetheless, knowledge of the effects of CNP inclusion on the properties of starch films is not fully elucidated. This paper reviews the influences of various concentrations of CNP, sizes of CNP, and other additives on the mechanical, thermal, barrier, antimicrobial, antioxidant, biodegradability, and cytotoxicity properties of starch/CNP films as well as the mechanisms involved in relation to food packaging applications. The usage of starch/CNP films for active food packaging can help to reduce environmental issues and contribute to food safety and security.